Administracyjnoprawne aspekty zmian powtarzających się nazw ulic Wrocławia po II wojnie światowej - Jankowska, Marta (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The author of the article discusses the problem of changes in streets names in Wrocław introduced as a result of the territorial growth of the city after the Second World War. On each occasion the expansion of the territory of the city following the incorporation of successive neighbourhoods brought with it the need to solve the problem of two, often three or even four streets or squares with the same name in the city. The author has established the legitimacy and the legal basis of the changes. She presents the names themselves in an analytical manner, verifying each changed street name in terms of its linguistic or substantive correctness. In addition, she discusses the legislative path and the legal procedure applied in the introduction of the changes. She also points to the placement of names in the historical and political context, examines their social background and attempts to assess the validity of this type of changes, comparing them with solutions adopted in other countries of Europe
Keywords: nazwy własne polskie; prawo administracyjne; ulice; Wrocław